PENGGUNAAN TEKNIK SHOW NOT TELL DALAM MENINGKATKAN KEMAMPUAN MENULIS TEKS ANEKDOT - Maulana, Irpan; Kusmayanti, Desti (STKIP Subang, 2020)
The ability of students in writing is still low, especially in writing anecdotal texts, so we need a learning innovation that can improve students' abilities through the use of show not tell techniques. This study aims to improve students 'anecdotal text writing skills by applying the Show not tell technique, as well as describing the improvement in students' anecdotal text writing skills by applying the show not tell technique. The population in this study were all grade X students of SMA Negeri 1 Ciasem. The research method used was a pre-experimental design with One-Group Pretest-Posttest Design. Data collection techniques used in this study were writing tests. The data form of this research is in the form of an assessment of learning outcomes that illustrate the skills of students in writing anecdotal texts. Data analysis of test results is done by collecting data writing anecdotal texts, correcting, determining values ​​and processing values. The results showed a significant increase in anecdotal text writing test scores with pretest and posttest. Overall pretest results of students obtained an average value of 59.09 while the overall posttest results of students scored with an average of 78.27. Thus it can be concluded that the learning outcomes of writing anecdotal texts by using show not tell technique increases. Keywords: Writing, Anecdotal Text, Show Not Tell Technique